From a Strange Place. Challenges and Opportunities of Queer Feminist Theory - Gonçalves Soares, Ana Rita (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
This paper traces some of the main contributions of queer literary theory and criticism, developed in particular in the United States of America during the beginning of the 90s, emphasizing the Iberian reception of such texts and how they have contributed to shaping queer feminist theory as an analytical tool. Starting from the fertile semantic instability of the word “queer”, it is intended to provide an overall idea of the challenges and opportunities that come from approaching literary Medievalism from this excentric perspective. This study uses this analytical framework to highlight the strangeness underling the construction of universalizing History in literary texts and, by extension, of the discourses of exclusion that it has created and the cisheteropatriarchal power systems that perpetuate them.
Keywords: Queer; Feminism; History; Medievalism